The Role of Working Memory, Emotional Intelligence, and Task Type in L2 Writing - Mavrou, Irini; Bustos, Fernando (Círculo de Lingüística Aplicada a la Comunicación, 2025)
This study aimed to investigate to what extent working memory capacity (WMC) and emotional intelligence (EI) contribute to second language (L2) writing as assessed through measures of syntactic and lexical complexity and linguistic accuracy. Seventy-seven adult learners of Spanish took part in the study and performed two writing tasks, one about an emotional topic and the other one about a non-emotional topic. They also completed a self-reported measure of EI, the Trait Meta-Mood Scale, and three memory tasks, the Math Span Test, the Corsi Block-Tapping Task, and the Stroop Task. The results showed a negative correlation between emotional repair and visuospatial short-term memory capacity. Attention to emotions positively contributed to linguistic accuracy in both tasks, whereas linguistic distance between the first language of the participants and their L2 appeared to play a role in linguistic accuracy but only in the emotional task. Moreover, in the emotional task, WMC and emotional repair had a cumulative but opposing contribution — positive and negative, respectively — to the subordination density. Also, the hypothesis that the writing topic would have some influence on the lexico-morphosyntactic aspects of L2 writing was partly confirmed.